Case report: training neck and head control in children with chronic paralysis due to acute flaccid myelitis - Noonan-Eaton, Kathryn; Stout, Danielle; Goode-Roberts, MacKenzie; Leon Machado, Laura; Davis, Matthew; Behrman, Andrea L. (Frontiers in Rehabilitation Sciences, 2023)
Background: Acute flaccid myelitis (AFM) occurs rarely in children and adolescents yet damage to spinal motor neurons rapidly causes flaccid paralysis of limb, trunk, and neck muscles and possible respiratory failure. When neck muscles are weakened or paralyzed, a child loses head control severely compromising engagement with their environment. Compensation for lack of head control is achieved with external support devices attached to the wheelchair with no indication in the AFM literature for therapeutic efforts to restore head control. In this case series, we explored the possibility for recovery of head control when children with AFM received activity-based restorative therapies (ABRT) guided by principles targeting motor control. Case Description: Three children, two males and one female, ages 6, 9, and 7 with history of AFM-onset at 5, 7, and 4 years respectively, each lacking head control, either ventilator-dependent or with a tracheostomy, and all power wheelchair users via hand/foot control, enrolled in an ABRT out-patient program targeting activation of the neuromuscular system below the lesion. Methods: ABRT was provided 5 day/week: 1.5 hours of activity-based locomotor training and 1.5 hours of activity-based neuromuscular electrical stimulation. Results: An approach to address head/neck control developed iteratively across disciplines from complete compensation with passive external head support to emerging head control during diverse tasks, e.g., sitting, reaching, driving power chair, sit-to-stand, standing, stepping on treadmill, walking. Key principles identified and employed were a) passive facilitation, b) external head support, c) posterior head support, d) graded manual facilitation and, e) independent head control. Discussion: The recovery of head control in children with paralysis due to AFM may be accelerated when executing a step-wise progression to effectively target and challenge head control in parallel with ABRT. Treating three children with chronic lack of head control, a therapeutic strategy iteratively developed guided by scientific principles, e.g., segmental assessment of control, to promote recovery of head control. While encouraging, gaps for sensitive and responsive measurement instruments and treatment technologies persist to guide assistance, challenge, and promote independent head control.